The crystal structure of 13-(pyrazole-1-yl-4-carbonitrile)-matrine, C19H25N5O - Li Jun-Jie; Dong Fang-Yun; Zou Qi-Wen; Feng Yin; Yang Yu-Tao; Su Kai-Xuan; Huang Yong-Fu; Jiang Xu-Hong; Cheng Xing-An (Zeitschrift für Kristallographie - New Crystal Structures, 2021)
C19H25N5O, monoclinic, P21 (no. 4), a = 16.0600(2) Å, b = 5.3992(1) Å, c = 19.8514(2) Å, β = 94.260(1)°, V = 1716.58(4) Å3, Z = 4, Rgt (F) = 0.0350, wRref(F2) = 0.0908, T = 100.00(10) K.